Law, Land, and Gender in the Hebrew Bible: A Postcolonial Womanist Reading - Mathew, Shiju (Asia journal of theology, 2016)
In almost every religion, woman is identified and associated with the earth.1 The earth is depicted in female imagery. Although some Scripture passages glorify women, others portray them in a negative way. As the land is plowed to increase productivity, so, too, women are exploited for economic purposes (Ex 21:2-11).2 Women are regarded primarily as property and in terms of economic value (Gn 29:20-21; Dt 22:28-29, Ex 21:22-25). Many are aggressively exploited to satisfy the selfish ambitions of a few. The untold plight of women and their ongoing religious, cultural, social, and political struggles have resulted in the emergence of different movements. This article will investigate and examine the interconnection between law, land, and gender in the Hebrew Bible. To achieve this goal and to unveil the inner meaning, I will employ a postcolonial womanist approach. This approach will help us to investigate the position of women, their role in society and tradition, and how they face multiple oppressions of race and class, particularly the domination by colonial powers.